Superior Talent Development Strategy in Preparing Future Leaders During Change - Warman, M. Aditya; Maarif, M. Syamsul; Sukmawati, Anggraini; Affandi, Joko (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
Talent management development is directly related to the organization's future-readiness. Competent, loyal, passionate, and highly motivated employees are important assets as future leaders, meaning the right strategy is needed for increasingly global business development readiness. Therefore, this study aimed to analyze the talent management policy strategies that promote organizational justice, where data were analyzed using the Fuzzy Analytical Process (FAHP) method. The results showed that a superior talent policy strategy is important and should be implemented according to the organization’s needs to prepare future leaders. The strategy is essential in preparing future leaders during change by involving BPJSTK management, the Ministry of Manpower, and talent. It is important to ensure the effective implementation of a superior talent development model in line with the needs of future leaders. Keywords: fuzzy analytical process, talent management, superior talent, development strategy, future leader